RESPON KARYAWAN TERHADAP KEBIJAKAN KESELAMATAN KERJA PADA PT. ASRINDO CITRASENI SATRIA DURI - SARI, MONALISA ANJAS; ", Yoserizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
PT . Asrindo Citraseni Satria is a company engaged in the Well Drilling and Re- Employment ( Drilling and Workover ), Transportation Equipment for Rig Operations, Procurement / Rental Equipment ground transportation and marine transportation, procurement / construction equipment rental and construction services, facility maintenance services. The company established in 1991 which is prior to the year 2007 has been using before OHSAS rules which only use rules of the Government and the Constitution in carrying out a health and safety program. Problem: How to socialization and the imposition of sanctions in the safety PT.ACS Thorns ? And how do you respond / employee attitudes towards safety policies on PT.ACS Thorns ?This study aims to determine the dissemination and application of sanctions in safety at PT. ACS Duri. And to investigate the response / employee attitudes towards safety policy at PT. ACS Duri. This research is a quota random sampling with quantitative descriptive approach. Total population of 915 persons and the number of employees 45 samples taken by 5 %.The response comes from the response, which means the reply / response (reaction). Response in the process preceded a person's attitude is a tendency for attitude / willingness of a person to behave when faced with a particular stimulus. From the results of this research is conducted surveillance at this company is very good, it means the socialization goes well and the response of each employee owned company PT. Asrindo Citraseni Satria safety policy is very good. This caused the employee is able to accept all the rules set by the company.Keywords : Profile of PT. Asrindo Citraseni Satria, Response and Control.